Influence of dance therapy mode of intangible cultural heritage on children's emotional regulation and psychological wellbeing: a randomized controlled intervention study - Xuetao Liu; Shuwei Xie (Frontiers in Public Health, 2026)
Background Children's psychological problems frequently appear, and the exploration of coping schemes without drugs, physical and mental integration and cultural depth has attracted academic attention. The intangible dance contains rhythmic movements, group cooperation, emotional expression and cultural implications, which make it a powerful tool for psychological intervention. The research on the educational application of dance in the field of intangible cultural heritage mainly focuses on conventional art therapy and music intervention. It is still a relatively new research direction to apply dance to children's mental health. Target In this study, an orderly framework of dance therapy for intangible cultural heritage was built. This framework examines its effects on children's emotional regulation, anxiety, signs of depression, self-worth and social adaptability, and explores the actual impact and mechanism of this treatment model. Way In this study, a randomized comparative test program was carried out. A total of 100 children aged 6 to 12 with mild emotional sensitivity, social maladjustment, increased stress level or attention disorder were randomly assigned to the experimental group (receiving ICH dance therapy intervention) and the control group (receiving routine psychological group counseling), and each group included 50 subjects. The intervention period is 16 weeks, including 12 weeks of structured dry expectation and 4 weeks of follow-up observation, so the implementation of intervention measures will be carried out three times a week, and the time will be maintained in the range of 35–45 min. The intervention scheme used in this study is composed of six links, including rhythmic exercise, emotional expression dance, rhythm relaxation exercise, collective dance interaction, cultural element integration and self-emotional examination. Emotional detection covers adjustment, anxiety level (GAD-7), depression score (PHQ-9), self-esteem status, social integration, participation consistency and emotional stability standards. In the field of data analysis, the implementation of repeated measurement analysis of variance is carried out, and the correlation is discussed with the help of Pearson correlation coefficient. Result After carrying out the experimental program, the members of the treatment group showed better promotion compared with the reference group in many aspects. Its emotional management has been improved, anxiety has been reduced, depression has been alleviated, self-worth has been enhanced, and social integration ability has also improved. Statistical tests have proved that these differences are significant. The study observed significant time effect and interaction effect between groups and time, and the improvement of emotional adjustment ability was positively correlated with the improvement of social adaptability and self-esteem, and the correlation coefficient was greater than 0.70, and the statistical test results were significant. There was no obvious bad mood or physical symptoms in the intervention stage. Conclusion The dance therapy mode of intangible cultural heritage has a significant positive impact on children's emotional adjustment ability and psychological and social development. This intervention will integrate physical activities, emotional release, group participation and cultural identity to enhance children's mental health, and open up a non-medical intervention path with structure, safety and cultural connotation. This study provides the necessary theoretical basis and practical support for the integration of mental health cultivation, aesthetic cultivation and the persistence of intangible cultural heritage in the child growth intervention system.